Data processing based on the privacy-preserving vector for wireless sensor networks - Wei-ni ZENG; Ya-ping LIN; Ye-qing YI; Shi-ming HE; Peng CHEN (Tongxin xuebao)
To solve the privacy disclosing problem during the data processing phase of wireless sensor networks,a dis-tributed mechanism was proposed.Privacy-preserving vector (vector for short) was constructed.Moreover,lightweight method for vector generation and novel method for using the vector were also presented.Thus,the methods were able to solve the privacy-preserving problem for various data processing funtions such as max/min and data compression effi-ciently.An algorithm based on data hiding and slice was given and then the vector was able to be generated securely and dynamically.Extensive analyses and experiments show that the mechanism is more robust to node compromise attack and thus can preserve privacy more efficiently.Moreover,the mechanism consumes less power.